The plankton community of a young, eutrophic, Antarctic saline lake - Bell, Elanor M.; Laybourn-Parry, J. (1999)
A shallow, saline lake (Rookery Lake) close to the sea and surrounded by a penguin rookery was investigated during the austral spring and summer of 1996/1997. The proximity to the sea means that the lake is likely to have been formed recently during isostatic uplift. Inputs of carbon and nutrients from the penguin rookery have rendered Rookery Lake eutrophic compared with other brackish and saline lakes in the Vestfold Hills. Chlorophyll a concentration, bacterioplankton, heterotrophic nanoflagellate and phototrophic nanoflagellate abundances were all significantly higher than in other non-enriched lakes. The high productivity created seasonal anoxia during winter and spring below ice cover. The ciliate community resembled the marine community, and was dissimilar to that seen in older saline lakes within the Vestfold Hills. Thus Rockery Lake provides valuable evidence of the impact of natural eutrophication on an Antarctic lake, as well as of the evolution of the typical microbial community which dominates the older lakes of the Vestfold Hills.